Spatiotemporal characteristics of organic contaminant concentrations and ecological risk assessment in the Songhua River, China. Issue 11 (7th October 2015) - Wang, Ce; Cyterski, Mike; Feng, Yujie; Gao, Peng; Sun, Qingfang
Abstract : To control source pollution and improve water quality, an understanding of the spatiotemporal characteristics of organic contaminant concentrations in affected receiving waters is necessary. Abstract : To control source pollution and improve water quality, an understanding of the spatiotemporal characteristics of organic contaminant concentrations in affected receiving waters is necessary. The Songhua River in northeast China is the country's third-largest domestic river and loadings of organic contaminants along an industrialized section have made it the focal point of a national pollution reduction plan. In addition to water quality issues, management of the Songhua River basin must also address local economic development, aquatic ecosystem sustainability and political relationships with Russia. In three periods spanning 2006 to 2010, eight polycyclic aromatic hydrocarbons (PAHs) and eight phenols were measured in surface waters at ten monitoring sites along the river. A generalized linear model (GLM) was used to characterize water quality at different sites and time periods. Chemical concentrations of the organic compounds showed significant sinusoidal seasonal patterns and the concentrations declined significantly from 2006 to 2010, possibly due to management practices designed to control water pollution. A critical body residue analysis showed that water concentrations measured during the winter of 2007 across all monitoring sites, but especially at S1-Shaokou and S2-Songhuajiangcun, presented a high risk for fish species. The spatiotemporal characteristics of water quality and estimated ecological risks shown here add to the body of knowledge to develop policies on industrial output and pollution management strategies for the Songhua River basin.